Sex chromosome pentasomy 49,XXXXY connected with hypothyroidism. Case report - Elżbieta Wójcik; Ryszard Ślęzak; Ewa Głąb; Beata Wikiera; Anna Noczyńska (Pediatric Endocrinology, Diabetes and Metabolism)
49,XXXXY syndrome is a very rare sex chromosomes polysomy, which is always connected with dysmorphic appearance, hypergonadothrophic hypogonadism and mental retardation. In this report we describe the clinical, biochemical, hormonal, radiological and developmental status of the patient with 49,XXXXY syndrome, referred to our department at the age of 12 months becauseofunderdeveloped external genitalia. Subclinical hypothyroidism and severe scoliosis could further disturb his development.